2019
DOI: 10.1182/blood-2019-125764
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human Gene Therapy Study of AAVhu37 Capsid Vector Technology in Severe Hemophilia A

Abstract: Background: Gene therapy for hemophilia A has the potential to reduce the treatment burden for care-providers and patients, by eliminating the need for regular factor VIII (FVIII) prophylaxis through the long-term expression of endogenous FVIII at levels sufficient to provide bleed protection. BAY 2599023 (AAVhu37FVIII) is a non-replicating adeno-associated virus (AAV) vector, based on the AAV serotype hu37, which contains a single-stranded DNA genome encoding a B-domain deleted FVIII, under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…As outlined in Tables 2 and 3 , there are 20 clinical trials approaching, including a handful of pivotal trials and the first pending licensing application (Harrington et al., 2020, WFH Virtual Summit, conference). 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 The field has largely converged on the use of systemically administered AAV vectors for hepatocyte expression of coagulation factors VIII (FVIII) and IX (FIX). 144 Although AAV efforts predominate, lentiviral vectors for either systemic infusion 157 , 158 or ex vivo transduction of hematopoietic stem cells 159 , 160 , 161 or induced pluripotent stem cells 162 are being pursued preclinically or as a phase I clinical trial.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined in Tables 2 and 3 , there are 20 clinical trials approaching, including a handful of pivotal trials and the first pending licensing application (Harrington et al., 2020, WFH Virtual Summit, conference). 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 The field has largely converged on the use of systemically administered AAV vectors for hepatocyte expression of coagulation factors VIII (FVIII) and IX (FIX). 144 Although AAV efforts predominate, lentiviral vectors for either systemic infusion 157 , 158 or ex vivo transduction of hematopoietic stem cells 159 , 160 , 161 or induced pluripotent stem cells 162 are being pursued preclinically or as a phase I clinical trial.…”
Section: Main Textmentioning
confidence: 99%
“… 144 , 145 , 149 , 152 Unlike FVIII-SQ, FIX-R338L differences are not gene-therapy specific, suggesting the assay discrepancies are related to FIX-R338L biochemistry. 192 , 201 , 211 , 212 The understanding of which assay best predicts in vivo hemostatic function of hepatocyte-derived FVIII/FIX-R338L is relevant to guide clinical management because sustained FVIII:C/FIX:C, depending on the assay used, crosses clinical thresholds of mild/moderate hemophilia, 152 , 155 normal FVIII:C/FIX:C (Harrington et al., 2020, WFH Virtual Summit, conference), 145 , 146 and supratherapeutic FVIII:C/FIX:C (Harrington et al., 2020, WFH Virtual Summit, conference). 145 Preliminary FVIII antigen data correlate with CSA-determined FVIII:C, 153 whereas preliminary phenotypic data supporting OSA-determined FVIII:C correlate with hepatocyte-derived FVIII in vivo function, 152 suggesting that hepatocyte-derived FVIII may be more easily converted from its procofactor to cofactor state.…”
Section: Main Textmentioning
confidence: 99%
“…Preliminary report of the phase I/II open-label, first time in human dose-finding study (NCT03588299) showed that two patients had measurable expression of endogenous FVIII and an early read-out of haemostatic efficacy at the starting dose of 0.5 × 10 13 vg/kg. 53 …”
Section: Evolution Of Aav Vector Gene Therapy For Haemophiliamentioning
confidence: 99%
“…AAVhu37 (BAY 2599023, Bayer) is being studied in a Phase I study. Thus far, two patients with severe HA without inhibitors have been treated with a dose of 0.5E13 gc/kg with no AEs and have achieved FVIII levels of 5–15% (NCT0358829) 61 …”
Section: Gene Therapymentioning
confidence: 99%